2011
DOI: 10.1111/j.1365-2230.2010.03864.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging of mid-dermal elastolysis

Abstract: Mid-dermal elastolysis (MDE) is a rare disease that is characterized histopathologically by selective loss of elastic tissue in the mid dermis. We aimed to assess MDE using noninvasive skin imaging techniques in vivo. We examined both the lesional and adjacent healthy skin of a woman with the reticular variant of MDE, using confocal scanning laser microscopy, optical coherence tomography (OCT) and high-frequency ultrasound (HFUS). The median diameter of blood vessels at the top of dermal papillae was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…However, it should be emphasized that the design of the present study does not evaluate variables that may explain the relationship among these parameters. Moreover, the evaluated data of lean controls in this study are in accordance with previous reports on RCM measurements concerning skin microcirculation 27 and skin morphometry. 28 In conclusion, impaired local microvascular function along with histomorphological remodeling of the human skin was evaluated in overweight.…”
Section: Discussionsupporting
confidence: 91%
“…However, it should be emphasized that the design of the present study does not evaluate variables that may explain the relationship among these parameters. Moreover, the evaluated data of lean controls in this study are in accordance with previous reports on RCM measurements concerning skin microcirculation 27 and skin morphometry. 28 In conclusion, impaired local microvascular function along with histomorphological remodeling of the human skin was evaluated in overweight.…”
Section: Discussionsupporting
confidence: 91%
“…Since Gambichler’s review in 2010, there have been 13 new publications regarding MDE, but these cover only 10 novel clinical cases, as Gambichler and colleagues wrote three distinct publications all regarding the same clinical patient (Gambichler and Skrygan, 2013, Gambichler et al, 2010, Scola et al, 2011). Furthermore, there were two publications on MDE that did not report new clinical cases (El-Khoury et al, 2014, Tong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive imaging methods, such as coherence tomography and high frequency ultrasound, are potential new modalities recently reported to be of use in evaluating MDE (Scola et al, 2011). Further, multiphoton microscopy, which uses near-infrared light to visualize deep tissues and exploit autofluorescent extracellular matrix fibers, has been used to calculate and three-dimensionally quantify elastic fibers (Tong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies retrieved from the literature report on a wide variety of pathologic conditions of the skin. Overall, 8 studies described cutaneous diseases, 15,18,19,24,26,29,31,32 3 studies reported on cutaneous manifestations in course of systemic diseases, 17,28,34 and 7 studies described UHFUS aspect of malignant lesions. 13,16,[20][21][22]27,33 Chen et al 15 differentiated lichen sclerosus et atrophicus from morphea trough UHFUS examination, as the UHFUS finding of a hypoechoic band corresponding to the presence of severe lymphedema oriented the diagnosis.…”
Section: The Study Of Skin Diseasesmentioning
confidence: 99%